An empirical study of the impact of lean construction techniques on sustainable construction in the UK. Issue 1 (2014) - ,; ,; ,
<x xml:space="preserve">Abstract</x> Purpose – The contribution of lean construction techniques in sustainable construction cannot be over emphasised, as sustainable development is now enshrined in government policy. In addition, lean construction is now faced with the challenges of sustainable development, continuous improvement, waste elimination, a stronger user focus, increased value for money along with high quality management of projects and supply chains, and improved communications. This paper presents an exploratory study from extant literature and the results of the use of questionnaire survey among construction participants to explore the contribution of implementing lean construction techniques in sustainable construction. Design/methodology/approach – Surveys of UK‐based construction professional were conducted. The data collected were analysed with SPSS 19.0 version software using the percentile method, Cronbach's α reliability test, Kruskal Wallis test, Kendall's coefficient of concordance and one sample t‐test. Findings – Results from this study indicate that there are several benefits associated with implementation of lean construction and sustainable construction. The overall perspective of professionals within the construction industry, according to questionnaire survey, shows that benefits such as improved corporate image and sustainable competitive advantage, improved process flow and productivity, improvement in environmental quality and increased compliance with customer's expectations are realised following integration of principles of lean construction and sustainable construction within construction industry. Just‐in‐time, visualisation tool, value analysis, daily huddle meetings and value stream mapping are the most common lean tools/techniques for enabling sustainability. This study also identified several areas of linkage between lean and sustainability such as waste reduction, environmental management, value maximisation, and health and safety improvement among others. Originality/value – The originality of this paper lies in its consideration of lean construction principles to better understand its impact on sustainable construction. This research contributes to the awareness of the benefits that can be derived from the implementation of lean construction in sustainable construction within the construction industry.